Determining Success Criteria and Success Factors for International Construction Projects for Malaysian Contractors - Alashwal, A.M.; Fareed, N.F.; Al-Obaidi, K.M. (UTS ePRESS, 2017)
The success of international construction projects is fraught with various challenges such as competitiveness, lack of resources, versatile global economy, and specific conditions in the host country. Malaysian contractors have been venturing into global construction market since early 1980s. However, their venturing was not successful all the time. The number of international projects awarded to Malaysian contractors has reduced drastically during the past decade. Taking advantage of this experience, this paper aims to identify the success criteria and success factors of international construction projects. The data was collected from 120 respondents using a questionnaire survey and analysed using principal component analysis and regression analysis. The results revealed three principal criteria of project success namely, Management Success, Functional Success, and Organisation Success. The main components of success factors include Team Power and Skills, Resource Availability, External Environment, Organisation Capability, Project Support, and Project Organisation. Further analysis emphasized the importance of strong financing capacity of contractors, project social environment, and competence of the project manager in achieving project success. The results of this paper can serve as a guideline for contractors and project managers to achieve success in this context. Future studies may provide in-depth analysis of success criteria and success factors specific for construction project type and host-country location.